ChemInform Abstract: Nitroalkenes in the Synthesis of Carbocyclic Compounds. Issue 47 (6th November 2014) - Halimehjani, Azim Ziyaei; Namboothiri, Irishi N. N.; Hooshmand, Seyyed Emad
Abstract Review: [16 refs.